PENDIDIKAN ESTETIKA MELALUI SENI BUDAYA DI FAKULTAS BAHASA DAN SENI UNIVERSITAS NEGERI SEMARANG (Harmonia: Journal of Arts Research and Education, 2009)
This research is aimed to give an image of aesthetic education implementation through art inLanguages and Arts Faculty in Semarang State University. Applied method in this research isqualitative method. Data collection technique are done by observation, inter view, anddocumentation. Analyzing data is done by using interactive analysis. Technique of checkingrelevance data done by using triangulation. The result of this research shows that aestheticeducation implementation through art in Languages and Arts Faculty are done in form of formaland non-formal aesthetics. Formal aesthetic education are done by all of students in languagesand arts faculty through art materials. Non-formal aesthetics education are done by academicconsists of students, lecturers, employees, as well as the head of faculty. Non-formal estheticseducation mainly are done as a coordinating institution of students’ activity unit. Aestheticseducation for lecturers, employees, as well as the head of faculty mainly done through artappreciation and creation by watching art exhibition, watching art performances, doing artactivities which held by faculties and majors events.Kata kunci : seni budaya, estetika, pendidikan, apresiasi, kreasi